Telemedicine as a Tool to Provide Family Conferences and Palliative Care Consultations in Critically Ill Patients at Rural Health Care Institutions: A Pilot Study. (June 2015) - Menon, Prema R.; Stapleton, Renee D.; McVeigh, Ursula; Rabinowitz, Terry
Background: Many critically ill patients who transfer from rural hospitals to tertiary care centers (TCCs) have poor prognoses, and family members are unable to discuss patient prognosis and goals of care with TCC providers until after transfer. Aim: Our TCC conducted teleconferences prior to transfer to facilitate early family discussions. Design/Setting: We conducted a retrospective review of these telemedicine family conferences among critically ill patients requested for transfer which occurred from December 2008 to December 2009 at our TCC. Outcomes for each patient and detailed descriptions of the conference content were obtained. We also assessed limitations and attitudes and satisfaction with this intervention among clinicians. Results: During the 12-month period, 12 telemedicine consultations were performed. Of these patients, 10 (83%) died in the 30 days following the request for transfer. After the telemedicine consultation, 8 (67%) patients were transferred to our TCC from their respective hospitals, while 4 (33%) patients continued care at their regional hospital and did not transfer. Of the patients who transferred to TCC, 7 (88% of those transferred) returned to their community after a stay at the TCC. Conclusion: This study demonstrates that palliative care consultations can be provided via telemedicine for critically ill patients and that adequate preparation and technical expertise are essential. Although this study is limited by the nature of the retrospective review, it is evident that more research is needed to further assess its applicability, utility, and acceptability.